Relative Roles of TGF-β and IGFBP-5 in Idiopathic Pulmonary Fibrosis - Sureshbabu, A.; Tonner, E.; Allan, G. J.; Flint, D. J. (Pulmonary Medicine, 2011)
Although most evident in the skin, the process of scarring, or fibrosis, occurs in all major organs because of impaired epithelial self-renewal. No current therapy exists for Idiopathic pulmonary fibrosis. The major profibrotic factor is TGF-β1 and developing inhibitors is an area of active research. Recently, IGFBP-5 has also been identified as a profibrotic factor, and studies suggest that, while both TGF-β1 and IGFBP-5 activate mesenchymal cells to increase collagen and fibronectin production, their effects on epithelial cells are distinct. TGF-β1 induces cell death and/or EMT in the epithelial cells, exacerbating the disruption of tissue architecture. In contrast, IGFBP-5 induces epithelial cell spreading over collagen or fibronectin matrices, increases secretion of laminin, the epithelial basement membrane, and enhances the survival of epithelial cells in nutrient-poor conditions, as exists in scar tissue. Thus, IGFBP-5 may enhance repair and may be an important target for antifibrotic therapies.